ESTIMATION OF DYNAMIC STRESSES IN LAST STAGE STEAM TURBINE BLADES UNDER REVERSE FLOW CONDITIONS - Кондратюк, Олег Леонідович; Скоркін, Антон Олегович; Литвинова, Олена Олегівна (Eastern-European Journal of Enterprise Technologies, 2012)
The last stage blades of steam turbine, which are at high variable voltage at low volumetric flow of steam is considered. A method for evaluation of stable and dynamic loads at low volumetric flow of steam is representation.